Garnet-Type Nanophosphors for White LED Lighting - Cantarano, Alexandra; Ibanez, Alain; Dantelle, Géraldine (Frontiers in Materials, 2020)
In this article we present a short review of the main wet chemical methods developed for the preparation of Ce3+-doped Y3Al5O12 (YAG:Ce) nanocrystals for their use as nanophosphors in LED lighting technology : combustion, co-precipitation, sol-gel, modified-Pechini and solvothermal routes. We highlight the key synthesis steps and discuss them in the view of the size, crystal quality and agglomeration state of the obtained nanocrystals. The photoluminescence internal quantum yield of these nanocrystals is also discussed in light of their morphology. In addition, we report on other garnet-type nanophosphors (Gd3Sc2Al3O12, (Gd,Y)3Al5O12, etc) doped with lanthanide ions (Ce3+, but also Eu3+ or Dy3+) developed with the goal of obtaining a warmer white light. The spectroscopic properties of these nanophosphors, in particular their emission range, is discussed in relation with the doping nature, doping concentration and crystal field of the host matrices.